Fluid Management in Dengue -Insights from Bedside - Jayasekera, Krishnatha (Bangladesh Journal of Medicine, 2024)
Dengue fever, a prevalent tropical viral illness transmitted by mosquitoes, poses a substantial burden on healthcare systems in Southeast Asia. Despite the increase in case density annually there is a noticeable downward trend in mortality rates in Sri Lanka. The pathophysiological hallmark of severe dengue is plasma leakage, leading to potentially life-threatening complications such as shock and organ failure. Key aspects of clinical care include early recognition of warning signs, monitoring of clinical parameters, and tailoring fluid therapy to individual patient needs. Optimizing fluid management is essential for reducing morbidity and mortality associated with severe dengue infection. Key decisions on fluid management are individualized with intense monitoring of vital parameters. The amount and type of fluid administered to maintain adequate perfusion while preventing fluid overload are based on the bed side clinical and sonographic assessment. This case-based discussion provides an overview of current fluid management strategies in various clinical stages of dengue highlighting the common pitfalls that may arise during management of complicated dengue patients. It is of utmost importance that we acquire the insight into the judicious fluid management during critical phase of dengue to minimize morbidity and mortality. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 130-131